Pengaruh Latihan Zig-Zag Run terhadap Peningkatan Kelincahan Pemain Futsal pada Club Rocket FC - Lativa Lativa; Bambang Hermansah; Mutiara Fajar (SENTRI: Jurnal Riset Ilmiah, 2026)
This research is based on the low agility ability as a Club Rocket FC futsal player which is seen when players change direction quickly when playing. Based on the results of observation and shuttle run test, there are still many players who are in the category of lack of agility. This research aims to find out the effect of zig-zag run training on improving the agility of futsal players in Club Rocket FC. The method used in this study is an experimental method with a one-group pretest-posttest design. The research sample consists of 30 determined players determined using a saturated sampling technique. The measurement of agility is done using a shuttle run test instrument. The zig-zag run training program is given for 6 weeks with a practice frequency of 3 times every week. Data analysis was carried out using the Shapiro-Wilk normality test and the paired sample t-test - with the help of SPSS version 27. The results of the study showed an increase in agility after being given a zig-zag run training treatment. This can be seen from the average pretest value of 14,8887 seconds which decreased to 13.9197 seconds in the posttest. In addition, the results of the hypothesis test obtained a significance value (Sig. 2-tailed) of 0.000 < 1.697261, so that Ha received Ho was rejected. Based on these results, it can be concluded that zig-zag run training has a significant influence on improving the agility of futsal players at Club Rocket FC.